KONTROVERSI PERSOALAN IMÃMAH DI KALANGAN KAUM SYIâAH - Hatta, Mawardy (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2016)
Imamate is the main Shiite doctrine. They use the term Imam as a substitute for a degree of prophet office after his death. Shiites in particular Imami Itsna Asyari and Ismailism found an eligible priest to be after Prophet Muhammadâs death is Ali bin Abi Talib. While the Prophet never specify who should be a priest, he only mentions the qualities of a priest and accidental properties that are owned by Ali bin Abi Talib, so Ali should be chosen become a priest. Thinking about the Imamate, Shiites refer to events that occurred in Ghadir Khum, where the prophet has returned from the Farewell Pilgrimage stopped in Ghadir area Arafah. Then, he appointed and inaugurated Ali bin Abi Thaib to be his successor as priest. This event is believed by a group of Imami Itsna Asyari and Ismailism as the basis for the appointment of Ali as priests. In addition they also use Qurâanic verses that are understood and interpreted according to their version, as a proposition or argument in strengthening the doctrine of the Imamate. While the group did not seem to wear Zaidiyyah the arguments and the Ghadir event.